2021
DOI: 10.3390/healthcare9040378
|View full text |Cite
|
Sign up to set email alerts
|

Nominal Groups to Develop a Mobile Application on Healthy Habits

Abstract: The new pandemic-lockdown situation has caused empowerment of new technologies; mobile phones and computers have gained further importance. Homes have become the new educators of health since health education has decreased or stopped during the pandemic. The lack of knowledge in the child and adolescent population about how to incorporate healthy habits in their daily lives, along with the rise of health devices and the introduction of healthcare in the syllabus, has led to the realization of the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…This coincides with the rise of the use of mobile devices (mainly smartphones and tablets) and with the scientific evidence of the impact of healthy apps on public health. In the current context, it is important to emphasize that different studies have reported that apps are helping in the struggle against COVID-19 [ 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…This coincides with the rise of the use of mobile devices (mainly smartphones and tablets) and with the scientific evidence of the impact of healthy apps on public health. In the current context, it is important to emphasize that different studies have reported that apps are helping in the struggle against COVID-19 [ 14 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 43 ]. Finally, we analyzed mobile apps because these tools allow hospitals to make their health education campaigns more dynamic and creative [ 28 ]. Additionally, thanks to these apps, patients can control medical metrics and improve their healthcare outcomes [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Promoting health education constitutes a social priority, especially when people face pandemics, as was recently the case with the COVID-19 outbreak [ 27 ]. To efficiently manage this pandemic, three main types of organizations were involved: international organizations, governments, and citizens [ 28 ]. International organizations worked together to analyze test results, symptoms, and treatments, and based on that, they implemented health education campaigns to curve the COVID-19 pandemic [ 29 ].…”
Section: From Patients’ Education To Health Education Based On Mobile...mentioning
confidence: 99%
See 1 more Smart Citation
“…This app was designed by researchers of the Universities of Seville and Huelva [ 25 ] to promote healthy lifestyles with a global approach on health. It fits the needs and concerns of young people, as the design process was initiated with the development of nominal groups with which relevant topics to address were identified [ 26 ].…”
Section: Introductionmentioning
confidence: 99%